Carbon encapsulation of MoS2 nanosheets to tune their interfacial polarization and dielectric properties for electromagnetic absorption applications. Issue 2 (10th December 2020) - Ye, Song; Xie, Aming; Wu, Fan; Cai, Zhiwei; Liu, Xu; Tao, Tian; Chang, Gang; He, Yunbin
Abstract : Electrical conductivity and interfacial polarization are two crucial factors that affect the electromagnetic absorption (EMA) performance of dielectric semiconductors. Abstract : Electrical conductivity and interfacial polarization are two crucial factors that affect the electromagnetic absorption (EMA) performance of dielectric semiconductors. In this work, we report an efficient surficial-coating strategy to tune the interfacial polarization and dielectric properties of molybdenum disulfide (MoS2 ) nanosheets. In this strategy, undoped and N-doped carbon films have been successfully coated on MoS2 nanosheets through a hydrothermal deposition and pyrolysis process. The EMA performance of MoS2 nanosheets was improved remarkably after carbon coating. It is found that the maximal absorption reaches −56.97 dB at 5 GHz while the effective absorption bandwidth (below −10 dB) reaches 5.44 GHz. A model referring to elevated electrical conductivity and improved interfacial polarization was used to explain the mechanism of enhanced EMA performance. This research greatly supports the development of novel MoS2 based high-performance EMA materials.